Claiming Chinatown: Asian Australians, Public Art and the Making of Urban Culture. Issue 3 (3rd July 2017) - Ang, Ien
ABSTRACT: Chinatowns have traditionally functioned as ethnic enclaves that were despised by the dominant Western culture, while functioning for Chinese immigrants as a refuge from the hostile white society they were surrounded by. In today's globalised world, the meaning of Chinatowns has been transformed, as they have become more open, hybrid and transnational urban spaces, increasingly interconnected within the broader Asia-Pacific region. For Asian Australians, Chinatown may be a site of conflicting memories of Australia's racist history and of cultural marginalisation and ethnic survival, but it is also—in today's multicultural and cosmopolitan age—an area to be claimed for the expression of new Asian Australian identities. In Sydney's Chinatown, public art projects by Asian Australian artists such as Jason Wing and Lindy Lee articulate some of the complexities and ambiguities of what it means to be Asian in Australia today.